Cognitive and affective aspects of thigmotaxis strategy in humans - KALLAI, Janos (Institutional Knowledge at Singapore Management University, 2007)
The present article describes the cognitive and emotional aspects of human thiginotaxis (a wall-following spatial strategy) during exploration of virtual and physical spaces. The authors assessed 106 participants with spatial and nonspatial performance-based learning-memory tasks and with fear and anxiety questionnaires. The results demonstrate that thiginotaxis plays a distinct role at different phases of spatial learning. The 1st phase shows a positive correlation between thigmotaxis and general phobic avoidance, whereas there is no association between thigmotaxis and general phobic avoidance during later phases of learning. Furthermore, participants who underperformed in working memory tests and in a spatial construction task exhibited greater thiginotaxis and a higher potential for fear response. Findings are interpreted in the framework of interactions among emotion-, action-, and knowledge-controlled spatial learning theories.